Search for a scalar partner of the top quark in the all-hadronic tt[bar] plus missing transverse momentum final state at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (The European physical journal. C, Particles and fields, 2020)
A search for direct pair production of scalar partners of the top quark (top squarks or scalar third-generation up-type leptoquarks) in the all-hadronic $$t{\bar{t}}$$ plus missing transverse momentum final state is presented. The analysis of 139 $$\hbox {fb}^{-1}$$ of $${\sqrt{s}=13}$$ TeV proton-proton collision data collected using the ATLAS detector at the LHC yields no significant excess over the Standard Model background expectation. To interpret the results, a supersymmetric model is used where the top squark decays via $${\tilde{t}} → t^{(*)} {\tilde{χ }}^0_1$$, with $$t^{(*)}$$ denoting an on-shell (off-shell) top quark and $${\tilde{χ }}^0_1$$ the lightest neutralino. Three specific event selections are optimised for the following scenarios. In the scenario where $$m_{{\tilde{t}}}> m_t+m_{{\tilde{χ }}^0_1}$$, top squark masses are excluded in the range 400-1250 GeV for $${\tilde{χ }}^0_1$$ masses below 200 GeV at 95% confidence level. In the situation where $$m_{{\tilde{t}}}\sim m_t+m_{{\tilde{χ }}^0_1}$$, top squark masses in the range 300-630 GeV are excluded, while in the case where $$m_{{\tilde{t}}}< m_W+m_b+m_{{\tilde{χ }}^0_1}$$ (with $$m_{{\tilde{t}}}-m_{{\tilde{χ }}^0_1}\ge 5$$ GeV), considered for the first time in an ATLAS all-hadronic search, top squark masses in the range 300-660 GeV are excluded. Limits are also set for scalar third-generation up-type leptoquarks, excluding leptoquarks with masses below 1240 GeV when considering only leptoquark decays into a top quark and a neutrino.
Im Titel steht der zweite Buchstabe t mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelzeichen
ATLAS collaboration: G. Aad, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, A. Kugel, M. Mkrtchyan, F. Napolitano, P.S. Ott, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 04.05.2022